2015
DOI: 10.1063/1.4921054
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of excess oxygen for environmentally stable amorphous In-Si-O thin-film transistors

Abstract: We discuss the environmental instability of amorphous indium oxide (InO x )-based thin-film transistors (TFTs) in terms of the excess oxygen in the semiconductor films. A comparison between amorphous InO x doped with low and high concentrations of oxygen binder (SiO 2 ) showed that out-diffusion of oxygen molecules causes drastic changes in the film conductivity and TFT turn-on voltages. Incorporation of sufficient SiO 2 could suppress fluctuations in excess oxygen because of the high oxygen bond-dissociation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Doping with metal cations (X = Ga 3+ , Zn 2+ , Si 4+ , Hf 4+ ) to yield ternary or quaternary oxides of formula IXO or IXZO (Z = Zn) is a conventional strategy for In 2 O 3 amorphization, Such transition and post-transition metal ions with large spherically symmetrical n s-orbitals ( n ≥ 4) provide a dispersive conduction band for electron transport, even in the amorphous state. From Shanmugam’s theory, Lewis acid strength ( L = z / r 2 , where z = the atomic core charge number and r = the ionic radius) and dopant metal-oxide bond dissociation energy ( E M–O ) are key parameters that stabilize MOs against O vacancy formation.…”
Section: Inroductionmentioning
confidence: 99%
“…Doping with metal cations (X = Ga 3+ , Zn 2+ , Si 4+ , Hf 4+ ) to yield ternary or quaternary oxides of formula IXO or IXZO (Z = Zn) is a conventional strategy for In 2 O 3 amorphization, Such transition and post-transition metal ions with large spherically symmetrical n s-orbitals ( n ≥ 4) provide a dispersive conduction band for electron transport, even in the amorphous state. From Shanmugam’s theory, Lewis acid strength ( L = z / r 2 , where z = the atomic core charge number and r = the ionic radius) and dopant metal-oxide bond dissociation energy ( E M–O ) are key parameters that stabilize MOs against O vacancy formation.…”
Section: Inroductionmentioning
confidence: 99%
“…Cation doping of gate dielectrics (e.g., La in AlO x ) has been used to mitigate the substantial capacitance–frequency dependence at low frequencies (∼10 Hz) and yields hysteresis-free transistor performance and reliable mobilities . Other than MO cation doping, anion doping has also been explored to modulate MO properties, especially for MO semiconductors. Moreover, this laboratory recently found that incorporating fluoride (F) in both the solution-processed semiconductor (InO x ) and dielectric (AlO x ) films promotes metal coordination and impurity removal, leading to high-performance amorphous oxide TFTs . However, we did not explore the details of how anion doping enhances the dielectric stability at low frequencies or study the doping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…11(b)]. 119) These results indicate that the TFTs become environmentally stable when using ISO-10 films sputtered with low PO2. Compared with the ISO-3 TFTs, the reliability of the ISO-10 TFTs was significantly improved, although the μi was reduced.…”
Section: Change In the Carrier Transport Mechanismmentioning
confidence: 75%